Factors that influence the performance management system in the Municipality of KwaZulu-Natal - Rylan Marie; Njabulo Khumalo (Cogent Business & Management, 2024)
South African government spheres were initiated to enforce and implement the performance management systems going forward and identify poor-performing personnel. The current state indicates that most municipality employees do not meet their deadlines, produce incomplete work, have high absenteeism, and have several complaints received. Research reveals that a performance system is a strategy to motivate employees to achieve institutional goals by rating each other’s contributions. The paper focuses on identifying the factors that influence the performance system within the municipality in the province of KwaZulu-Natal in South Africa. The paper adopted a quantitative approach and constructed a questionnaire to collect data from 80 municipal employees. A simple random method was used to offer all participants with equal opportunity to participate. All collected data was analysed using SPSS version 27. The paper revealed that managing performance, upskilling, motivating, engaging with employees, job satisfaction, training and development, and two-way processes were the factors that influenced the municipality’s performance management system. The paper recommends that management provide timely and regular feedback to employees regarding their performance and treat the performance management system as ongoing versus once a year.